Analisis Faktor-Faktor yang Berhubungan dengan Pemilihan Tempat Persalinan Tahun 2016 (Studi di Wilayah Puskesmas Perawatan Suban Kabupaten Tanjung Jabung Barat) - Titin Prihatin; M. Zen Rahfiludin; Sri Winarni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Maternal mortality as much as 60% occurs in the birth process, Maternal death is closely related to place of childbirth is take place. One effort to reduce the risk of morbidity and mortality of mothers and infants is to improve the childbirth of nakes in health care facilities,  in Community Health Care Center Suban, As much as 74,65% mothers do childbirth at home (non-health facilities). The purpose of this research is to analize factor related to choice place of childbirth in Community Health Care Center Suban Area District Tanjung Jabung Barat. The method of this research is analytical correlation with cross sectional approach. Population in this research mother maternity in january - october 2016 counted 422 people with the number of samples interviewed by 80 maternity mothers. The instrument used was a closed questionnaire. Hypothesis proved by chi square test, α=5% and CI=95%. The result of this research is 83,8% mother choosing maternity at home (non-health facilities). Factors studied were mother maternity education (pvalue=0,031), Family income (pvalue=0,665), Mother maternity knowledge (pvalue=0,569), attitude (pvalue=0,909), and family support (pvalue=0,004). Factors related to the choice of place of childbirth In the work area of Community Health Care Center Suban,is mother maternity knowledge and family support.